The impact of the waiver of marriage announcement on the validity of the contract - Almabrouk, Mahdi Amin Mousa; Muhammad Husni, Ahmad; El-Seoudi, Abdel Wadoud Moustafa Moursi (Design for Scientific Renaissance (DSR), 2013)
This paper discusses the subject of waiver of a right related to both of the spouses which is the announcement of marriage. The research question is: if the couple holds the marriage contract in the presence of two witnesses, but without the knowledge of others, will their marriage be true? One objective of the research is to prove that the registration of the marriage contract in the presence of two witnesses at the competent Sharia court is a legitimate declaration of marriage. This research found, after studying the evidences of majority of scholars and the Maliki doctrine, that the contract and the condition are correct in the abovementioned case.